Ziziphus rugosa Leaf: Pharmacognostical Characters and Anti-Inflammatory Properties against Carrageenan-Induced Paw Edema - Krishna, Enugurthi Hari; Saravanan, Kamatchi Sundara; Jays, Judy (Borneo Journal of Pharmacy, 2024)
Ziziphus rugosa belongs to the family Rhamnaceae, which includes many flowering species, primarily trees and shrubs, and sometimes vines. This study aims to describe the pharmacognostic characteristics and potential anti-inflammatory properties of Z. rugosa leaf. The pharmacognostical and preliminary phytochemical studies were performed following standard procedures. Acetone, ethanol, and aqueous extracts were screened for anti-inflammatory potential using the carrageenan-induced paw edema model. Ziziphus rugosa was identified by its evergreen nature, recurved hooks, and drupe-type fruits. Leaves are elliptic/rounded with cordate base exhibiting a dark green glossy upper surface and pubescent lower surface. The leaf exhibited a dorsiventral nature in the transverse section, covering trichomes, collenchyma, sclerenchyma patch, and calcium oxalate crystals as key histological characters. Anamocytic stomata, covering trichomes, crystals, and fragments of vessels, are the imperative elements in powder. The extracts contain carbohydrates, alkaloids, glycosides, tannins, saponins, phenolic compounds, proteins, and flavonoids. The acetone extract at 400 and 200 mg/kg displays a maximum inflammation inhibition of 56.96% and 48.77% among the extracts, and the standard diclofenac sodium inhibits inflammation by 65.61% at 24 hours. The altered liver superoxide dismutase, glutathione, and malondialdehyde levels in the positive control group are significantly near normal in the treatment groups. The histopathological studies of treated animals show significant protection against paw and liver tissue damage. Pharmacognostical study outcomes aid in the identification of species along with ascertaining standardization parameters. Further fractionation of acetone extract followed by isolating compounds responsible for the anti-inflammatory activity would provide an alternative to managing inflammation.